The State of the Art of the Tunisian Apidae Fauna (Hymenoptera: Anthophila) - Ben Khedher, Hassib; Braham, Mohamed; Chaieb, Ikbal (Sociobiology, 2022)
Based on a review of the available literature, the state of the art and a checklist of the fauna of the Apidae family of Tunisia is presented. The first list of the species of the family is given. 184 species and subspecies belonging to 19 genera, 12 tribes and three subfamilies were listed. Distribution of recorded taxa from Tunisia and from the world is provided. Apinae is the subfamily with the highest species richness with 89 species. Nomada has the highest number of species represented by 62 taxa. The Tunisian East center is the least species-diversified regions with only 16 species and subspecies reported so far. Five species are endemic to Tunisian fauna. Eight Nomada and one Anthophora species were collected from Tunisia, but their identity should be re-confirmed. The presence of Thyreomelecta sibirica (Radoszkowski, 1893) in Tunisia is doubtful and a re-examination and confirmation are needed.